Espelho, espelho meu, existe alguém mais doida ou santa do que eu? Representações para a mulher em crônicas de Martha Medeiros - Lima, Letícia Oliveira de (2015)
This work aims to investigate through the analysis of contextual, lexicogrammatical and semantic-discursive elements the representations for women in chronicles of the book Doidas e Santas by Martha Medeiros. Therefore, it is based on the theoretical perspective of Systemic Functional Linguistics, particularly on the experiential ideational metafunction and interpersonal metafunction of the Systemic Functional Grammar (HALLIDAY; MATTHIESSEN, 2014) and on Appraisal System (MARTIN; WHITE, 2005). The corpus of this research consists of 20 chronicles of the book Doidas e Santas by Martha Medeiros. The methodological approach consisted of two steps: contextual analysis and linguistic analysis. The first referred to the contextual information that pervades the texts from the corpus. The second referred to the following methodological steps: a) segmentation of the texts into clauses; b) selection of clauses concerning women; c) classification of clause elements into process, participant and circumstance; d) identification and analysis of lexicogrammatical functions played by woman, followed by the interpretation of the data obtained from this analysis in search of representations; e) verification and analysis of occurrences of appraisal; and f) categorization of the representations for women from the data obtained in the analysis. The results of the analysis of the chronicles that constitute the corpus pointed to the existence of 13 representations for women, which were systematically presented from five daily themes found in these chronicles: i) loving relationship; ii) physical appearance; iii) maternity; iv) expression of desires and v) expression of feelings. With these results, we can conclude that there is a diversity of women's behaviors that constitute different ―types‖ of contemporary women, but all still somewhat constrained by socially established standards.